2009 16th Working Conference on Reverse Engineering 2009
DOI: 10.1109/wcre.2009.13
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Package Coupling and Cycle Minimization

Abstract: Abstract-Object-oriented (OO) software is usually organized into subsystems using the concepts of package or module. Such modular structure helps applications to evolve when facing new requirements. However, studies show that as software evolves to meet requirements and environment changes, modularization quality degrades. To help maintainers improve the quality of software modularization we have designed and implemented a heuristic search-based approach for automatically optimizing inter-package connectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 28 publications
1
65
0
1
Order By: Relevance
“…In total 10 data-sets are formed. Each data-set comprises of 6 traditional packagelevel metric described by R.C Martin [2],4 package quality metrics defined by Abdeen et al [10] for fault-proneness of packages, source code bug warnings of priority 1 identified by FindBugs and code rules violation warnings of priority 1 reported by PMD.…”
Section: Data Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total 10 data-sets are formed. Each data-set comprises of 6 traditional packagelevel metric described by R.C Martin [2],4 package quality metrics defined by Abdeen et al [10] for fault-proneness of packages, source code bug warnings of priority 1 identified by FindBugs and code rules violation warnings of priority 1 reported by PMD.…”
Section: Data Setsmentioning
confidence: 99%
“…Post-release fault data of subjects was obtained from public repositories, i.e., Eclipse Bug Data 9 and PROMISE 10 . For package modularization metrics, experiment study consists of 23 versions of two different open source software systems.…”
Section: Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitchell and Mancoridis [Mitchell and Mancoridis 2006] use the same technique in Bunch, a tool supporting automatic system decomposition. Search-based approaches are also used in several other works [Harman et al 2002;Praditwong et al 2011;Seng et al 2005;Abdeen et al 2009]. In particular, Harman et al [Harman et al 2002] and Seng et al [Seng et al 2005] use a single-objective genetic algorithm to improve the subsystem decomposition of a software system, where the fitness function is defined using a combination of quality metrics.…”
Section: Related Workmentioning
confidence: 99%
“…It should be noted that we do not oppose fingerprints to other techniques; on the contrary, we see them as complementary. For example, independently of this work and this article, we developed complementary tools to help dealing with packages such as Package Blueprints (which is based on a zoom-out visualization and ordering of internal references between packages) [DPS + 07]; Orion (which supports the prediction of change impact) [LDDK09] and a Simulated Annealing search-based technique to help maintainers find good alternative modularizations [ADSA09]. Maintainers can then use the fingerprints to compare the results, understand the alternatives, and choose the most suitable modularization.…”
Section: Hints For Code Improvements and Fingerprint Limitationsmentioning
confidence: 99%